Terpene-Based Phytochemicals as a Novel Strategy for Biofilm Disruption and Enhanced Wound Healing - Perera, Thanusha; Natarajan, Satheesh Babu; Kalusalingam, Anandarajagopal; Choudhury, Shudipta; Ramachandran, Kamaleswaran (Trends in Sciences, 2026)
Wound healing is a complex, multi-phase process involving hemostasis, inflammation, proliferation, and remodeling. Chronic wounds, including diabetic ulcers and pressure sores, often stall in the inflammatory phase due to persistent infections, oxidative stress, and impaired tissue regeneration. Microbial biofilms, particularly from Staphylococcus aureus and Pseudomonas aeruginosa, shield bacteria from host defenses and antibiotics, contributing to the majority of chronic infections and hospital-acquired infections. This review evaluates the antibiofilm and antimicrobial potential of terpene-based phytochemicals and examines their formulation into nanoemulsion-based delivery systems. Published studies were analyzed for mechanisms of biofilm disruption, bacterial inhibition, and enhancement of antimicrobial activity via nanoemulsions. Terpene phytochemicals disrupt biofilm architecture, inhibit bacterial proliferation, compromise cell membrane integrity, and interfere with quorum sensing and adhesion processes. When delivered in nanoemulsions, their solubility, stability, and bioavailability are improved, enhancing antimicrobial efficacy. These compounds also promote tissue repair and regeneration, addressing both infection control and wound healing. By simultaneously targeting biofilm-protected pathogens and supporting tissue regeneration, terpene-based phytochemicals offer a biocompatible, nature-inspired therapeutic strategy for chronic wound management. Their combined antibiofilm, antimicrobial, and tissue-regenerative actions underscore their potential as next-generation agents for advanced wound care. HIGHLIGHTS Dual-action potential: Terpene phytochemicals disrupt biofilms and support tissue regeneration, addressing chronic wound challenges. Enhanced efficacy via nanoformulations: Nanoemulsions and nanocarriers improve stability, solubility, and bioavailability, enabling targeted delivery. Synergy with conventional therapies: Terpenes potentiate antibiotics, antimicrobial peptides, and photodynamic therapy, reducing resistance and accelerating healing. Advanced delivery strategies: Microneedles, hydrogels, and scaffold-based systems provide controlled, localized, and sustained release. Translational and regenerative promise: Integration with microbiome modulation, growth factors, and stem cell therapies positions terpenes as next-generation, patient-centered therapeutics. GRAPHICAL ABSTRACT